Layout selection for optimal urban sewer network design (2024)
This paper is an extension of the suggestions made by Bermúdez (2023) to the methodology of sewer network design of Duque, Duque, Aguilar & Saldarriaga (2020), where it was determined that the selection of the layout may reduce the cost of design by Saldarriaga, Zambrano, Herrán & Inglesias-Rey (2021). The new approach may consider different features from a network by using selection criteria based of the topography, topology and inlet flows tried on 77 study cases, and a procedure was developed to understand which criteria could get the lowest costs. In the investigation it was found that each network may have its own criterion to determine the minimum cost possible based on characteristics as the topography, topology and inlet flows. In this research, the data were able to select exactly two criteria that would get almost every case inside the 1% of the minimum cost, excluding some cases that were specified by the features of the network and covered with other criteria. Finally the research gave an standardize use of the criteria to select the layout with lower costs.